Posted by **Brett** on Tuesday, September 18, 2007 at 11:39pm.

1: Suppose John had a utility function of U=X^2/3Y^1/3 . Derive Johns demand function from his utility function showing all the necessary steps.

i know that the MUx=MUy and first i derive the equation to

2/3X^-1/3 1/3Y^-2/3

then im stuck i need help with the simplification

## Answer this Question

## Related Questions

- Economics - Ive been stuck on this forever now if someone could please walk me ...
- Micro Economics - Briefly explain the following: (a)Economic cost and accounting...
- economics - 1.. Suppose that U(x; y) = min(x; y) with px = 1 and py = 1. ...
- economics - Suppose a monopolist faces production function Q = 3KL and demand ...
- economics - 1. Chipo has the following utility function of 2 goods Pies (X) and ...
- economics - 1. Chipo has the following utility function of 2 goods Pies (X) and ...
- economics - 1. Chipo has the following utility function of 2 goods Pies (X) and ...
- microeconomics - Suppose a person has a utility function U=YX. What is the ...
- economics - Suppose a person has a utility function U=YX. What is the minimum ...
- Microeconomics - Given the utility function U(C,T) = 3C+2T A budget constraint ...